Rotavirus incapable of NSP6 expression can cause diarrhea in suckling mice. (31st May 2022) - Fukuda, Saori; Kugita, Masanori; Higashimoto, Yuki; Shiogama, Kazuya; Tsujikawa, Hanako; Moriguchi, Kyoko; Ito, Naoto; Sugiyama, Makoto; Nagao, Shizuko; Murata, Takayuki; Taniguchi, Koki; Komoto, Satoshi
Abstract : The group A rotavirus (RVA) genome comprising 11 double-stranded RNAs encodes six structural proteins (VP1-VP4, VP6, and VP7) and six non-structural proteins (NSP1-NSP6). Among these 12 rotaviral proteins, NSP6 has been less studied as to its function. We previously prepared a recombinant NSP6-deficient RVA derived from simian strain SA11-L2 by reverse genetics, and found that the NSP6-deficient virus grew well in cell culture, although its growth was less abundant than that of the parental SA11-L2 strain. In this study, we examined the potency of a recombinant RVA incapable of NSP6 expression to cause diarrhoea in suckling mice. The suckling mice infected with the NSP6-deficient virus apparently experienced diarrhoea, although the symptom was milder and the duration of diarrhoea was shorter than in the mice infected with the authentic SA11-L2 strain. Thus, together with the results obtained for cultured cells in the previous study, it can be concluded that NSP6 is not necessarily required for replication and pathogenicity in vitro and in vivo .